Predictive modeling of apple slice drying: Integrating temperature, thickness, and shrinkage dynamics - Mehdi Moradi; Reza Raeesi; Sadegh Rashidi; Mahdi Keramat-Jahromi (PLoS ONE, 2026)
This study investigates the effects of drying temperature and slice thickness on the drying kinetics, shrinkage, moisture diffusivity, and color of Golden Delicious apple slices. Drying experiments were conducted in triplicate at 50°C, 60°C, and 70°C with slice thicknesses of 2, 4, and 6 mm using a controlled cabinet dryer. Statistical analysis using ANOVA confirmed that both factors significantly affected drying behavior and quality attributes. Drying time decreased with higher temperatures and thinner slices, with slice thickness exerting the stronger influence. Shrinkage decreased and effective moisture diffusivity increased under these conditions. Multivariate regression models accurately predicted shrinkage and moisture diffusivity (R² > 0.97), while Finite Element Modeling (FEM) closely matched experimental moisture transfer. Color evaluation showed that the combination of 70°C and a 4-mm slice thickness produced the lowest total color change (ΔE). Although high temperatures can accelerate browning, in this case the shorter drying time at 70°C limited discoloration, making this specific condition optimal for visual quality. These findings provide practical guidance for designing energy-efficient drying processes that maintain product quality, while future work should explore anisotropic shrinkage modeling, energy use, and hybrid drying technologies to enhance process performance.